(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Traffic congestion poses a significant challenge in urban areas of emerging nations, such as India. The increase in urban population and the expansion of the middle-class demographic are key factors that contribute substantially to the escalating quantity of cars within metropolitan areas. The presence of traffic congestion on roadways ultimately leads to a decrease in the speed of traffic, resulting in extended journey times. Consequently, this issue emerges as a prominent concern in urban areas. This study introduces an advanced traffic control system designed to facilitate the seamless passage of emergency vehicles. Every individual vehicle is equipped with a specialized radio frequency gadget. Radio frequency (RF) transmitter (Tx) and receiver (Rx) modules are utilized in ambulances and traffic signals, respectively. The system observes and records the movement of cars as they traverse a designated route within a predetermined time frame. Additionally, it is responsible for assessing the level of network congestion, which subsequently influences the duration of the green light for the given pathway. When an ambulance traverses a roadway, it activates the green signal light until it has completely cleared the signalized zone.